Lipid oxidation dysregulation: an emerging player in the pathophysiology of sepsis - Muniz-Santos, Renan; Lucieri-Costa, Giovanna; Almeida, Matheus Augusto P. de; Moraes-de-Souza, Isabelle; Brito, Maria Alice Dos Santos Mascarenhas; Silva, Adriana Ribeiro; Gonçalves-de-Albuquerque, Cassiano Felippe (Frontiers in Immunology, 2023)
Sepsis is a life-threatening organ dysfunction due to an abnormal host's response to infection. Millions of people are annually affected worldwide. Derangement in the inflammatory response is crucial to sepsis pathogenesis. However, metabolism, coagulation, and thermoregulation alterations also occur in septic patients. In particular, fatty acid mobilization and oxidation changes may assume the protagonist's role in sepsis pathogenesis. Thus, lipid oxidation and free fatty acid (FFA) are potentially valuable markers for sepsis diagnostic and prognostic. Herein, we discuss inflammatory and metabolic dysfunction during sepsis, focusing on fatty acid oxidation (FAO) alterations in the liver and the muscle (skeletal and cardiac) and implications in sepsis development.